Improving Job Search Skills: A Field Experiment on Online Employment Assistance - Guglielmo Briscese; Giulio Zanella; Veronica Quinn (Institute of Labor Economics (IZA), 2020)
Finding a job requires effective search skills to engage successfully with employers with vacancies. In a field experiment, we test a website that supplements such search skills by providing editable resume and cover letter templates as well as tips on how to look and apply for jobs. Exposure to the website was randomized among about 2,700 job seekers in Australia. The intervention increased job-finding rates, particularly among job seekers aged 35-50 (up to 8 percentage points), with larger effects for women within this age group (up to 10 percentage points). The quality of job matches improved too.
Keywords: J08; J64; J68; 330; online job search assistance; search skills; active labor market policy